2000
DOI: 10.1037/0021-9010.85.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and continuous improvement in the United States, Mexico, Poland, and India: Predicting fit on the basis of the dimensions of power distance and individualism.

Abstract: Although variations in national cultures predominate as explanation for the belief that universal approaches to management do not exist, there have been few reports of systematic studies. Data from employees of a single firm with operations in the United States, Mexico, Poland, and India were used to test the fit of empowerment and continuous improvement practices with national culture. Using the theoretical constructs of individualism-collectivism and power distance, the authors predicted that the practices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
3
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 354 publications
(197 citation statements)
references
References 54 publications
6
184
3
4
Order By: Relevance
“…Hui, Au & Fock (2004) examining the moderating effect of power distance on the relationship between empowerment and job satisfaction across 33 countries generally, and speci ically between Canadian and Chinese hotel employees, show that the relationship between empowerment and job satisfaction was stronger in countries with lower power distances. Similarly, Robert, Probst, Martocchio, Drasgow & Lawler (2000) examining the moderating role of culture in the relationship between employee empowerment and job satisfaction, found that empowerment was negatively associated with satisfaction in India but positively associated but positively associated the United States, Mexico, and Poland. Based on the concepts of individualism/collectivism and power distance, these authors suggest that such practices would be more common in some cultures than in others thereby affecting in job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hui, Au & Fock (2004) examining the moderating effect of power distance on the relationship between empowerment and job satisfaction across 33 countries generally, and speci ically between Canadian and Chinese hotel employees, show that the relationship between empowerment and job satisfaction was stronger in countries with lower power distances. Similarly, Robert, Probst, Martocchio, Drasgow & Lawler (2000) examining the moderating role of culture in the relationship between employee empowerment and job satisfaction, found that empowerment was negatively associated with satisfaction in India but positively associated but positively associated the United States, Mexico, and Poland. Based on the concepts of individualism/collectivism and power distance, these authors suggest that such practices would be more common in some cultures than in others thereby affecting in job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disimpulkan bahwa penghargaan secara signifikan berhubungan dengan kepuasan kerja karyawan. Struktur penghargaan suatu organisasi mempunyai pengaruh terhadap kepuasan dan kesetiaan karyawan (Lawler 2000).…”
Section: Analisis Dan Pembahasanunclassified
“…Sin embargo, y como se ha señalado, no hay soluciones universales en la gestión y dirección del personal y, el éxito de determinadas prácticas depende del ajuste entre las creencias y los valores inherentes a los modelos que se quieren introducir y los de los grupos y personas implicados en los cambios (Robert, Probst, Martocchio, Drasgow y Lawler, 2000).…”
Section: Introductionunclassified